TOURIST PERCEPTION OF THE AIDA MODELS IMPLEMENTATION IN THE MEDIA OF PROMOTION IN TOURISM ATTRACTION TESBATAN VILLAGE, KUPANG DISTRICT - Bagaihing, Martarida (TOURISM: Jurnal Travel, Hospitality, Culture, Destination, and MICE, 2020)
The Kupang Regency Government continues to make various efforts to increase tourism in its area. One of these efforts is providing information through media of promotion to attract tourists to visit Tesbatan Village. In this effort, it is necessary to identify tourists' perceptions of the AIDA (attention, Interst, Desire, Action) Model in the media of promotion of tourist attraction in Tesbatan Village, Kupang Regency, East Nusa Tenggara. This research is a type of qualitative research using descriptive analysis with the assessment categorization method based on the level of achievement of the respondents. Data collection using a questionnaire based on a Likert scale. The results showed that the perception of visitors about the AIDA Model in the media of promotion for tourist attraction in Tesbatan Village was based on each of the indicators, namely: (1) the element of Attention in the promotional media was categorized as poor with an average percentage of 55%, (2) the element of Interest in the promotional media it is categorized as good enough with an average percentage of 67%, (3) the element of Desire in the promotional media is categorized as good with an average percentage of 70%, (4) the element of Action in the promotional media is categorized as good with an average percentage of 68%.